An organic trimer molecule with carbon black as an active material for supercapacitor applications - Arjun Rego; Elliot Evans; Navid Noor; Storm Gourley; Alejandra Ibarra Espinoza; Amirhossein Foroozan Ebrahimy; Drew Higgins (Next Materials)
Quinone-based organic molecules show promise as electrode active materials for supercapacitor applications due to their reversible redox activity, high theoretical capacitances, low cost, nontoxicity, and renewability. The use of quinone containing molecules in supercapacitor applications faces challenges due to their low electrical conductivity and their high solubility in aqueous electrolytes that results in low cycling stability. This work addresses these limitations by proposing a novel quinone-composed material, N,N′-bis(2-anthra-quinone)]-perylene-3,4,9,10- tetracarboxydiimide (PDI-DAQ), as an organic molecule electrode for supercapacitors. PDI-DAQ was composited with a low-cost carbon substrate, Ketjenblack carbon black (CB), and demonstrated a specific capacitance of up to 318.6 F g−1 at 5 mV s−1 in 1 M H2SO4 electrolyte at an optimized mass ratio of 1:1 (PDI-DAQ to CB). This material had a capacity retention of 61.2 % after 10,000 cycles at 100 mV s−1. Ultimately, PDI-DAQ as a supercapacitor material demonstrates the performance advantages of covalently bonding redox-active quinone molecules and preparing a PDI-DAQ/CB OME through a simple preparation process.